Influence of Distance and Argon Flow rate on Pseudomonas aeruginosa Bacteria Exposed to Non thermal Plasma at Atmospheric Pressure - Abbas, Ibrahim Karim (Iraqi Journal of Science, 2022)
In this research, a type of gram negative bacteria was exposed to non-thermal plasma at a distance of (2 and 3 cm) from the plasma flow nozzle, with the use of an alternating power supply (5KHz), where exposure was made at two different voltages (4.9 and 8 kV). A negative gram of Pseudomonas aeruginosa bacteria was isolated and exposed to non-thermal plasma at different flow rates of argon gas whose value ranged from (1-5) liters/minute. The results showed that bacterial killing rate is directly proportional to distance while exposing the samples to non-thermal plasma, and the best factors by which a complete killing rate was obtained were at a distance of 2 cm with a voltage of 8 kV and a gas flow rate of 5 liters/min, while complete killing of bacteria was not achieved at a distance of 3 cm where the percentage was 95% at the same argon gas flow rate.